The Impact of Training and Organizational Culture on Marketing Employee Performance with Engagement as a Mediating Variable at PT Mentari Books Indonesia, Jakarta - Damhudi, Dedi; Pradiani, Theresia; Fathorrahman, Fathorrahman (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Performance is an important factor in achieving the goals of an organization, including a company. Good employee performance will lead to significant growth and help achieve company goals, such as increasing sales, expanding market share, and providing customer satisfaction. Good employee performance will support every company activity and broadly impact all stakeholders involved. This research aims to examine the effect of training and organizational culture on the performance of the marketing workforce with engagement as a mediating variable at PT Mentari Books Indonesia Jakarta. The sampling method used is the saturated sampling or census method, where all 58 employees in the marketing division of PT Mentari Books Indonesia Jakarta are used as samples for this study. The research results show that (1) training does not have a significant effect on the performance of the marketing workforce, (2) organizational culture does not significantly affect the performance of the marketing workforce, (3) training has a positive and significant effect on the engagement of the marketing workforce, (4) organizational culture has a positive and significant effect on the engagement of the marketing workforce, (5) engagement does not significantly affect the performance of the marketing workforce, (6) training does not affect performance through the engagement of the marketing workforce, and (7) organizational culture does not affect performance through the engagement of the marketing workforce.